Understanding the Effect of Impeller Configurations on Pullulan Production by Aureobasidium Pullulans RBF 4A3 - Kumar, Bhupender; Katoch, Anjula; Prasad, Gandham S.; Roy Choudhury, Anirban (Frontiers in Bioengineering and Biotechnology, 2019)
Mass transfer is one of the important factors in viscous fermentation processes, like production of pullulan. Impellers play a crucial role in maintaining homogeneity and better mass transfer conditions during the fermentation process.The present study attempted to evaluate the efficiency of impellers with diverse configurations during the pullulan fermentation. Initially, mass transfer coefficient of ten selected impellers were evaluated in aqueous system. Among these, three impellers namely Single Helical Ribbon, Rushton Turbine and Smith turbine impeller were found to be better and were further employed in pullulan fermentation process. The results suggested thatSingle Helical Ribbon impeller was able to provide 24% higher pullulan production as compared to Rushton Turbine and Smith turbine impellers. Single Helical Ribbon was able to maintain the critical demand of dissolved oxygen in fermentation broth. Therefore, it may be commented that Single Helical Ribbon impeller configuration is suitable for higher production of pullulan during the fermentation process.